Merck manual of medical information - Beers, Mark H. (NA, 2003)
Merck - a world leader in breakthrough medical research - has a long tradition of providing medical information to doctors, nurses, pharmacists and other healthcare professionals. Perhaps the best evidence of Merck's dedication is "The Merck Manual", the trusted medical reference doctors have used most since 1899. Although it is one of the most widely used sources of medical information in the world, it isn't written for the general public. "The Merck Manual of Medical Information - Second Home Edition" is completely revised and contains virtually all of the same information in "The Merck Manual" but in easy-to-understand, everyday language with a reader friendly format. The Second Home Edition is generously illustrated and covers all the important diseases and health issues that health-conscious readers want and need to know. Written by nearly 200 medical experts, the Second Home Edition has been completely revised and updated with some new features and recent developments in health and medicine.
Keywords: SPECIAL REFERENCE